Pembelajaran Mendalam dan Perkembangan Kognitif Anak Usia Dini Studi pada Proses Belajar Bermakna - Anny Harince Babys; Alfred Melkianus Toh (DIDASKO: Jurnal Teologi dan Pendidikan Kristen, 2026)
Early childhood cognitive development is the main foundation for learning success in the next stage of education and is greatly influenced by the quality of the learning process experienced by children. Learning at the Early Childhood Education level needs to be designed as a meaningful learning process that is in harmony with the characteristics of child development. This article aims to analyze the relationship between deep learning and early childhood cognitive development through the study of the process of meaningful learning. This study uses a descriptive qualitative approach with a literature review method on relevant scientific articles, both from accredited national journals and reputable international journals, which discuss deep learning, meaningful learning, and early childhood cognitive development. The data was analyzed through in-depth reading and systematic interpretation of the content of the article to identify thought patterns and tendencies of the research findings. The results of the analysis show that deep learning contributes significantly to early childhood cognitive development when learning focuses on meaningful, contextual, and child-centered experiences. The learning process that involves exploration, meaningful play, social interaction, and responsive teacher mentoring encourages children to build a more stable and sustainable understanding. Deep learning supports the development of basic cognitive abilities, intrinsic motivation, and early thinking functions. This article concludes that deep learning is a relevant pedagogical approach to improve the quality of early childhood learning through strengthening the meaningful learning process, so as to be able to build the foundation of children's cognitive development in a holistic and sustainable manner. Abstrak   Perkembangan kognitif anak usia dini merupakan fondasi utama bagi keberhasilan belajar pada tahap pendidikan selanjutnya dan sangat dipengaruhi oleh kualitas proses pembelajaran yang dialami anak. Pembelajaran pada jenjang Pendidikan Anak Usia Dini perlu dirancang sebagai proses belajar bermakna yang selaras dengan karakteristik perkembangan anak. Artikel ini bertujuan untuk menganalisis hubungan antara pembelajaran mendalam dan perkembangan kognitif anak usia dini melalui kajian terhadap proses belajar bermakna. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode kajian literatur terhadap artikel-artikel ilmiah yang relevan, baik dari jurnal nasional terakreditasi maupun jurnal internasional bereputasi, yang membahas pembelajaran mendalam, belajar bermakna, dan perkembangan kognitif anak usia dini. Data dianalisis melalui pembacaan mendalam dan penafsiran sistematis terhadap isi artikel untuk mengidentifikasi pola pemikiran dan kecenderungan temuan penelitian. Hasil analisis menunjukkan bahwa pembelajaran mendalam berkontribusi signifikan terhadap perkembangan kognitif anak usia dini ketika pembelajaran berfokus pada pengalaman yang bermakna, kontekstual, dan berpusat pada anak. Proses belajar yang melibatkan eksplorasi, bermain bermakna, interaksi sosial, dan pendampingan guru secara responsif mendorong anak membangun pemahaman yang lebih stabil dan berkelanjutan. Pembelajaran mendalam mendukung perkembangan kemampuan kognitif dasar, motivasi intrinsik, serta fungsi berpikir awal anak. Artikel ini menyimpulkan bahwa pembelajaran mendalam merupakan pendekatan pedagogis yang relevan untuk meningkatkan kualitas pembelajaran PAUD melalui penguatan proses belajar bermakna, sehingga mampu membangun dasar perkembangan kognitif anak secara holistik dan berkelanjutan.